PENGALAMAN IBU TENTANG TINDAKAN KEKERASAN PADA ANAK DI KELURAHAN KALIBEBER KECAMATAN MOJOTENGAH KABUPATEN WONOSOBO TAHUN 2012 - Taufik Hidayat; Ery Purwanti; Eka Riyanti (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2014)
The phenomena of violence especially child abuse is now widespread. This can give impact on child development in the future. Some people in certain communities view that it is reasonable action to educate children so that they often do violence on their children and they tend to be less aware of the bad impacts.The purpose of this study was to determine the mother's experiences of violence on children in Kalibeber Village Mojotengah Wonosobo. The research was conducted March to May 2012. The design of this study is a qualitative study with a phenomenological approach. The data were collected by the researcher who served as the interviewer. The results were analyzed in a way to organize and sort the data into patterns, categories and the basic outline of the unit.The results showed that mothers’ experience of violence in children was an action they gave to their children as they thought that their children had been doing bad things or naughty and disobey. Mothers did the forms of violence which they thought the actions were accepted such as as hitting, pinching, and yelling or scolding a child. By doing so, mothers thought that they would find their children more quiet and mischievous.In the effort to make children more discipline, mother does not have to use force or abusive ways. Mothers are expected to be more patient in educating their children. It is suggested to do more researches on the same object using a quantitative research design entitled factors that influence child abuse, so that there will be more respondents that can be researched.Keywords : mothers’ experience,Violence in children, child abuse